Pengolahan Biomassa Limbah menjadi Biobriket dan Pemanfaatannya sebagai Sumber Energi Alternatif - Noach, Yakob R.; Abdullah, Muhammad S; Yunus, Marthen; Amalo, Daud; Rosnah, Upik Syamsiar; Oematan, Gustaf; Arsa, I Gusti B. Adwita (GOTAVA Pengabdian Kepada Masyarakat, 2025)
This Community Service (PKM) activity aimed to enhance the knowledge and skills of the men’s fellowship of the Maranatha Oebufu congregation in utilizing waste biomass as an environmentally friendly alternative energy source. The main problems faced by the community were limited awareness of the potential of local biomass waste, such as goat manure and agricultural residues, and the lack of access to simple and applicable processing technologies. The activity was implemented using a participatory and empowerment-based approach through counselling, demonstrations, and hands-on training in producing bio-briquettes and related supporting equipment. Participants included members of the Service Support Unit (UPP), the Management Board (BP), and the men’s fellowship of Maranatha Oebufu congregation. The results showed a positive response and high level of participation from the community during the training process. Participants were able to produce bio-briquettes and operate simple equipment, including a pyrolysis drum, briquette mould, and briquette stove. Post-activity monitoring indicated that several households had begun independently producing and utilizing bio-briquettes made from palm shells and rice husks for cooking purposes. This activity demonstrates that participatory training in bio-briquette technology is effective in supporting household energy independence and community empowerment based on local resources.